TPACK AND ACADEMIC SUCCESS: A PLS-SEM STUDY IN INDONESIAN ISLAMIC UNIVERSITIES - Assidiqi, Hasby; Fauzi, Yusran; Zahrah (IAIN Ambon, 2025)
This study aims to analyse the influence of Technological Pedagogical Content Knowledge (TPACK) competence on the academic success of prospective mathematics teacher students at the State Islamic University of Antasari Banjarmasin. The research involved 70 students who had participated in Field Introduction Practice and were selected through purposive sampling. An explanatory quantitative approach was applied, employing Partial Least Squares Structural Equation Modelling (PLS-SEM) as the analysis technique. The findings indicate that TPACK competence has a positive and significant effect on students’ Cumulative Grade Point Average, although the effect size is relatively modest. In addition, the indirect effects of Pedagogical Content Knowledge (PCK) and Technological Pedagogical Knowledge (TPK) on GPA, mediated by TPACK, were also significant. These results demonstrate that the integration of content, pedagogy, and technology can improve teaching effectiveness and enhance student academic achievement. The conclusion highlights the importance of developing practice-based teacher education curricula grounded in integrative reflection to strengthen TPACK competence.